Clinical and molecular neuroimaging characteristics of Brazilian patients with Parkinson's disease and mutations in PARK2 or PARK8 genes - Barsottini, Orlando Graziani Povoas [UNIFESP] (2009)
OBJECTIVE: To describe clinical and neuroimaging (SPECT) characteristics of Brazilian patients with Parkinson's disease (PD) and mutations in PARK2 or PARK8 genes. METHOD: A total of 119 patients meeting clinical criteria for PD were evaluated. RESULTS: Of all patients studied, 13 had mutations in either PARK2 (n=9) or PARK8 genes (n=4). No statistically significant differences in clinical characteristics in both groups were seen. SPECT with [99mTc] TRODAT-1 showed significant differences between patient and control and the most remarkable difference was between PARK2 and control. CONCLUSION: The study found a frequency of mutation of 10.1% and it was most commonly seen in women. These patients had long disease course and high rates of dyskinesia after L-DOPA use. PARK8 patients did not have a relevant family history of PD.